Safety, reactogenicity and immunogenicity of two investigational pneumococcal protein-based vaccines: Results from a randomized phase II study in infants - Prymula, Roman; Szenborn, Leszek; Silfverdal, Sven-Arne; Wysocki, Jacek; Albrecht, Piotr; Traskine, Magali; Gardev, Asparuh; Song, Yue; Borys, Dorota (Vaccine, 2017)
INTRODUCTION: Vaccination with formulations containing pneumococcal protein antigens such as pneumolysin toxoid (dPly) and histidine-triad protein D (PhtD) may extend serotype-related protection of pneumococcal conjugate vaccines (PCVs) against Streptococcus pneumoniae. METHODS: This phase II, multi-center, observer-blind trial conducted in Europe (NCT01204658) assessed 2 investigational vaccines containing 10 serotype-specific polysaccharide conjugates of PHiD-CV and either 10 or 30µg of dPly and PhtD each. Infants randomized 1:1:1:1 received 4 doses of PHiD-CV/dPly/PhtD-10, PHiD-CV/dPly/PhtD-30, PHiD-CV, or 13-valent PCV (PCV13), co-administered with DTPa-HBV-IPV/Hib, at ages ∼2, 3, 4 and 12-15months. Occurrences of fever >40.0°C following primary vaccination with PHiD-CV/dPly/PhtD vaccines compared to PHiD-CV (non-inferiority objective), dose superiority, safety and immunogenicity were assessed. RESULTS: 575 children received primary vaccination, and 564 booster vaccination. The non-inferiority objective was met; no fever >40.0°C causally related to vaccination was reported during primary vaccination. Incidence of adverse events appeared similar between the 3 PHiD-CV groups. Serious adverse events were reported in 13, 9, 21 (1 related to vaccination), and 17 children in the PHiD-CV/dPly/PhtD-10, PHiD-CV/dPly/PhtD-30, PHiD-CV, and PCV13 groups, respectively. PHiD-CV/dPly/PhtD-30 was superior to PHiD-CV/dPly/PhtD-10 in terms of post-dose 3 anti-Ply and Anti-PhtD antibody levels. Anti-Ply and anti-PhtD antibody levels were higher in both PHiD-CV/dPly/PhtD groups than in controls and increased from post-primary to post-booster timepoint. Post-primary and booster vaccination, for each PHiD-CV serotype, ≥98.5% of participants in PHiD-CV/dPly/PhtD groups had antibody concentrations ≥ 0.2μg/mL, except for 6B (≥72.3%) and 23F (≥82.7%) post-primary vaccination. Similar results were observed in the PHiD-CV group. Immune responses to protein D and DTPa-HBV-IPV/Hib were within similar ranges for the 3 PHiD-CV groups. CONCLUSION: Both PHiD-CV/dPly/PhtD formulations co-administered with DTPa-HBV-IPV/Hib in infants were well-tolerated and immunogenic for dPly and PhtD antigens, while immune responses to serotype-specific, protein D and co-administered antigens did not appear altered in comparison to PHiD-CV group.
Keywords: Fever; séroskupina; Male; Immunization, Secondary; PhtD; Vaccines, Combined; Bacterial Proteins; vakcíny konjugované; Reactogenicity; Pneumococcal Infections; PHiD-CV vaccination; Infant; imunogenicita vakcíny; Pneumococcal protein; mužské pohlaví; Streptolysins; pneumokokové vakcíny; dPly; Pneumococcal Vaccines; Immunogenicity; vakcinace; sekundární imunizace; Infants; horečka; lidé; ženské pohlaví; Humans; kombinované vakcíny; kojenec; streptolysiny; bakteriální proteiny; Streptococcus pneumoniae; Vaccination; protilátky bakteriální; Serogroup; Immunogenicity, Vaccine; pneumokokové infekce; Female; Antibodies, Bacterial; Vaccines, Conjugate